Desenvolvimento de eletrodos de grafite modificados com nanopartículas e emprego na quantificação de sacarose - Santos, Luana Dalagrana dos (2022)
The quantification of sugars is an analysis of great importance in foods as it provides nutritional information about a product, which can influence consumer choice, and is also used as a quality parameter in some industries. There are many techniques and methods used for the determination and quantification of these compounds, but the vast majority of them are expensive, in addition to the need for more time for analysis. Thus, it is necessary to develop methods that quantify these compounds quickly and effectively. Thus, in this study an electrochemical method was proposed for the detection and quantification of sucrose through cyclic voltammetry, using carbon paste electrodes modified with copper or iron nanoparticles or carbon nanotubes. In addition, cyclic voltammetry was performed using a low-cost potentiostat designed for a Raspberry Pi single-board computer. The synthesized metallic nanoparticles were characterized by transmission electron microscopy (TEM), zeta potential, dynamic light scattering (DLS), mid-infrared spectroscopy (FTIR), X-ray diffraction (XRD), differential scanning calorimetry (DSC) and thermogravimetry (TGA). The constructed electrodes had their analytical performance tested with ferrocyanide and compared with a commercial glassy carbon electrode. Once good functioning was verified, they were used to obtain quantification models for sucrose. The quality of the models was tested by ANOVA and analytical figures of merit. Observing the values obtained for the adjusted R2 parameter, the models with the best adjustments were obtained for the commercial glassy carbon electrode (C vítreo) and the electrode made with the addition of copper oxide nanoparticles (Nano CuO). The values for the RMSE parameter for all models were similar, being all in the order of 10-4 mol L-1 . The lowest value for the inverse of the analytical sensitivity was obtained for the unmodified carbon paste electrode (C60%) with a concentration of 9.54 x 10-6 mol L-1 of sucrose, followed by the one made with copper oxide nanoparticle, 5.30 x 10-6 mol L-1 . The detection limits were lower for the electrodes made without modification (C60%) and with the addition of copper oxide nanoparticles (Nano CuO), in the order of 10-5 mol L-1 of sucrose. As for the limit of quantification, all electrodes made had very similar values, in the order of 10-2 mol L-1 of sucrose. In general, superior performance of the electrodes made of carbon paste was observed in relation to the commercial electrode of glassy carbon. Comparing the results obtained with previous studies, it is observed that the developed electrodes presented good sensitivity and the low cost of the electrochemical system stands out as the main advantage.